2016
DOI: 10.1083/jcb.201504043
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating pre-mRNA processing factors in the histone locus body facilitates efficient histone mRNA biogenesis

Abstract: Concentrating factors in nuclear bodies is thought to promote efficient gene expression. Tatomer et al. show that the histone locus body (HLB) concentrates pre-mRNA processing factors at replication-dependent histone genes, resulting in optimal 3′ end formation of histone mRNAs coupled with transcription termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 65 publications
4
119
1
Order By: Relevance
“…70 Similarly, a direct interaction between the NH 2 terminus of Lsm11 (in the U7 snRNP) and the NH 2 terminus of FLASH is necessary for pre-mRNA processing, but not for either U7 snRNP or FLASH to concentrate in the HLB. 72,73 In addition, the sequence in histone pre-mRNA that binds U7 snRNP is not required for U7 snRNP recruitment to the Drosophila HLB. 74 Instead, we found that the C terminus of FLASH, likely together with Mxc, is necessary for recruitment of U7 snRNP to the HLB.…”
Section: Self-organization Of the Hlbmentioning
confidence: 99%
See 4 more Smart Citations
“…70 Similarly, a direct interaction between the NH 2 terminus of Lsm11 (in the U7 snRNP) and the NH 2 terminus of FLASH is necessary for pre-mRNA processing, but not for either U7 snRNP or FLASH to concentrate in the HLB. 72,73 In addition, the sequence in histone pre-mRNA that binds U7 snRNP is not required for U7 snRNP recruitment to the Drosophila HLB. 74 Instead, we found that the C terminus of FLASH, likely together with Mxc, is necessary for recruitment of U7 snRNP to the HLB.…”
Section: Self-organization Of the Hlbmentioning
confidence: 99%
“…74 Instead, we found that the C terminus of FLASH, likely together with Mxc, is necessary for recruitment of U7 snRNP to the HLB. 72 Thus, there are interactions among HLB components involved in assembling the HLB that are distinct from the interactions required for histone mRNA biosynthesis. Such modularity could explain how a protein like FLASH participates directly and separately in HLB formation and pre-mRNA processing.…”
Section: Self-organization Of the Hlbmentioning
confidence: 99%
See 3 more Smart Citations